2008
DOI: 10.1089/rej.2008.0712
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Caloric Restriction or Exercise on DNA and RNA Oxidation Levels in White Blood Cells and Urine in Humans

Abstract: Excessive adiposity is associated with increased oxidative stress and accelerated aging. Weight loss induced by negative energy balance reduces markers of oxidation in experimental animals and humans. The long-term effects of weight loss induced by calorie restriction or increased energy expenditure induced by exercise on measures of oxidative stress and damage have not been studied in humans. The objective of the present study was to compare the effects of 20% caloric restriction or 20% exercise alone over 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 34 publications
4
45
1
2
Order By: Relevance
“…In this sense, our results support the hypothesis that a proper and balanced diet (even with a discrete loss of weight) exerts a protection role on genome, by enhancing DNA repair and/or preventing cell death and mutations as shown in previous studies [24,[39][40][41] .…”
Section: Discussionsupporting
confidence: 90%
“…In this sense, our results support the hypothesis that a proper and balanced diet (even with a discrete loss of weight) exerts a protection role on genome, by enhancing DNA repair and/or preventing cell death and mutations as shown in previous studies [24,[39][40][41] .…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, CRAN may extend the life span by decreasing the pro-inflammatory state: This condition attenuates insulin resistance and, concomitantly, decreases both metabolic disturbances and CVD. In humans, longterm CRAN not only decreases total and free IGF-1 concentrations but also reduces oxidative damage to both DNA and RNA measured in white blood cells [59]. In terms of cardiovascular health, CRAN has powerful protective effects against atherosclerosis.…”
Section: Insulin Proinflammatory State and Longevitymentioning
confidence: 99%
“…In several studies conducted in overweight human subjects, DR has been shown to improve a number of health outcomes, including a reduction in several cardiac risk factors (13)(14)(15) , an improvement in insulin-sensitivity (16) , and enhanced mitochondrial function (17) . Additionally, prolonged DR has also been found to reduce oxidative damage (18)(19)(20) . This way, findings of initial human clinical trials appear to support the promise of DR raised by animal studies, at least in overweight adults.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%